Agreement of Angiography-Derived and Wire-Based Fractional Flow Reserves in Percutaneous Coronary Intervention - Ai, Hu; Zheng, Naixin; Li, Le; Yang, Guojian; Li, Hui; Tang, Guodong; Zhou, Qi; Zhang, Huiping; Yu, Xue; Xu, Feng; Zhao, Ying; Sun, Fucheng (Frontiers in Cardiovascular Medicine, 2021)
Background: Coronary angiography-derived fractional flow reserve (caFFR) measurements have shown good correlations and agreement with invasive wire-based fractional flow reserve (FFR) measurements. However, few studies have examined the diagnostic performance of caFFR measurements before and after percutaneous coronary intervention (PCI). This study sought to compare the diagnostic performance of caFFR measurements against wire-based FFR measurements in patients before and after PCI. Methods: Patients who underwent FFR-guided PCI were eligible for the acquisition of caFFR measurements. Offline caFFR measurements were performed by blinded hospital operators in a core laboratory. The primary endpoint was the vessel-oriented composite endpoint (VOCE), defined as a composite of vessel-related cardiovascular death, vessel-related myocardial infarction, and target vessel revascularization. Results: A total of 105 pre-PCI caFFR measurements and 65 post-PCI caFFR measurements were compared against available wire-based FFR measurements. A strong linear correlation was found between wire-based FFR and caFFR measurements (r = 0.77; p < 0.001) before PCI, and caFFR measurements also showed a high correlation (r = 0.82; p < 0.001) with wire-based FFR measurements after PCI. A total of 6 VOCEs were observed in 61 patients during follow-up. Post-PCI FFR values (≤0.82) in the target vessel was the strongest predictor of VOCE (hazard ratio [HR]: 5.59; 95% confidence interval [CI]: 1.12 to 27.96; p = 0.036). Similarly, patients with low post-PCI caFFR values (≤0.83) showed an 8-fold higher risk of VOCE than those with high post-PCI caFFR values (>0.83; HR: 8.83; 95% CI: 1.46 to 53.44; p = 0.017). Conclusion: The study showed that the caFFR measurements were well-correlated and in agreement with invasive wire-based FFR measurements before and after PCI. Similar to wire-based FFR measurements, post-PCI caFFR measurements can be used to identify patients with a higher risk for adverse events associated with PCI.